Comprehensive analysis on the magnetic field error of a K–Rb–21Ne comagnetometer with low-frequency bias magnetic field sensitivity - Wu, Zhihong; Liu, Feng; Wang, Zhuo; Fan, Wenfeng; Pang, Haoying; Quan, Wei (Frontiers in Physics, 2023)
The spin-exchange relaxation-free comagnetometer (SERFC) have important research value compared to existing high-precision gyroscopes because of its extremely high theoretical limit sensitivity and long-term stability, in which one significant limiting factors is the magnetic field error. Firstly, the relationship between the magnetic field gradient and the nuclear spin relaxation mechanism is introduced into the frequency response and steady-state response models of SERFC. Then, a novel method for suppression of low-frequency magnetic field error based on the modified bias magnetic field sensitivity model is proposed. Finally, the effectiveness of the proposed suppression methods are demonstrated by optimizing the cell temperature, pump light power and compensation magnetic field gradient to increase the suppression factor by 72.19%,20.24% and 69.86% respectively, and the corresponding bias instability increased by 55.41%, 20.84% and 27.63%, respectively. This study contributes to improving the long-term zero bias stability of the SERFC.